STAGES OF MEDIA DEVELOPMENT PRIOR TO ARTIFICIAL INTELLIGENCE: FROM TRADITIONAL TO DIGITAL FORMATS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The integration of artificial intelligence (AI) into the media sector represents one of the most significant technological advancements of the 21st century. This article examines the technological evolution of artificial intelligence in media, categorizing its development from traditional media forms to digital formats. The discussion encompasses the transition from print media to digital platforms, the rise of audio and visual media, and the impact of the internet and social networks. The role of artificial intelligence in automating content creation, enhancing user engagement, and transforming media practices will also be addressed, highlighting the challenges and opportunities that arise in this context.